2013
DOI: 10.1017/s0007114512005545
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of a new organic selenium source v. seleno-yeast and mineral selenium sources on muscle selenium enrichment and selenium digestibility in broiler chickens

Abstract: Two experiments were conducted on broiler chickens to compare the effect of a new organic Se source, 2-hydroxy-4-methylselenobutanoic acid (HMSeBA; SO), with two practical Se additives, sodium selenite (SS) and Se yeast (SY). The relative bioavailability of the different Se sources was compared on muscle ( pectoralis major) total Se, selenomethionine (SeMet) and selenocysteine (SeCys) concentrations and apparent digestibility of total Se (AD Se ). In the first experiment, from day (d) 0 to d21, Se sources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 41 publications
(53 reference statements)
10
92
0
Order By: Relevance
“…It was further reported that yolk-Se concentration significantly increased due to organic and inorganic selenium supplementation and the greatest increase was observed by the group fed diet supplemented with organic selenium Leeson et al 2008;Attia et al 2010). Moreover, Briens et al (2013) stated that the different absorption manner between organic and inorganic selenium sources led to the different digestibility rates, with the inorganic source having a poorer digestibility than the organic form. Moreover, some other researchers stated that the addition of hens' diet with organic selenium not only improves their health status and productivity but can also be a natural way to yield functional food, respectively the production of eggs enriched with selenium (Fisinin et al 2008;Sara et al 2008;Hanafy et al 2009).…”
Section: Determination Of Selenium In Eggsmentioning
confidence: 96%
“…It was further reported that yolk-Se concentration significantly increased due to organic and inorganic selenium supplementation and the greatest increase was observed by the group fed diet supplemented with organic selenium Leeson et al 2008;Attia et al 2010). Moreover, Briens et al (2013) stated that the different absorption manner between organic and inorganic selenium sources led to the different digestibility rates, with the inorganic source having a poorer digestibility than the organic form. Moreover, some other researchers stated that the addition of hens' diet with organic selenium not only improves their health status and productivity but can also be a natural way to yield functional food, respectively the production of eggs enriched with selenium (Fisinin et al 2008;Sara et al 2008;Hanafy et al 2009).…”
Section: Determination Of Selenium In Eggsmentioning
confidence: 96%
“…Organic compounds such as seleniummethionine are the metabolic products generated through the absorption of biological bodies and the combination with organic compounds (Briens et al 2013;Du et al 2008). Previous studies have indicated that inorganic elements are converted into organic forms through utilization by microbes.…”
Section: Organic Ions Converted From the Inorganic Ions Of Dow By Micmentioning
confidence: 99%
“…In addition to organic Se compounds, other sources have been tested and utilized, such as selenium-enriched algae Scenedesmus quadricauda (selenium-enriched Scenedesmus biomass) (Umysova et al 2009;Skrivan et al 2010a), Se-enriched unicellular alga Chlorella (Travnicek et al 2007), Se-enriched yeast (Briens et al 2013;Nyquist et al 2013;Yuan et al 2013) or selenium chelate .…”
Section: Selenium Sources and Their Efficiencymentioning
confidence: 99%